The Swedish model - Ari Kokko (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The main characteristics of 'the Swedish model' are arguably related to the country's knowledge-intensive industry and its advanced welfare state. The purpose of this paper is to discuss the historical development of these two features of the Swedish economy. The first part looks at industrial development, highlighting both the reasons for the rapid industrialization in the late 19th century and the subsequent shift from raw materials to human capital and knowledge as the main competitive advantages. The second part turns to the development of welfare state, stressing the gradual increase in benefits and coverage as well as the emphasis on universal rather than means-tested benefits. The final part suggests some policy conclusions for today's developing countries and emerging economies.
Keywords: O14; O32; N34; 330; Sweden; industrialization; welfare state